Two single‐enantiomer amidophosphoesters: a database study on the chirality of (O)2P(O)(N)‐based structures. Issue 1 (28th December 2018) - Sabbaghi, Fahimeh; Pourayoubi, Mehrdad; Nečas, Marek; Damodaran, Krishnan
Abstract : The statistically identical chiral architectures constructed from N—H…O and C—H…O hydrogen bonds are discussed for a pair of optical isomers belonging to the amidophosphoester family. Abstract : The crystal structures of two single‐enantiomer amidophosphoesters with an (O)2 P(O)(N) skeleton, i.e. diphenyl [( R )‐(+)‐α‐methylbenzylamido]phosphate, (I), and diphenyl [( S )‐(−)‐α‐methylbenzylamido]phosphate, (II), both C20 H20 NO3 P, are reported. In both structures, chiral one‐dimensional hydrogen‐bonded architectures, along [010], are mediated by N—H…OP interactions. The statistically identical assemblies include the noncentrosymmetric graph‐set motif C (4) and the compounds crystallize in the chiral space group P 21 . As a result of synergistic co‐operation from C—H…O interactions, a two‐dimensional superstructure is built including a noncentrosymmetric R 4 4 (22) hydrogen‐bonded motif. A Cambridge Structural Database survey was performed on (O)2 P(O)(N)‐based structures in order to review the frequency of space groups observed in this family of compounds; the hydrogen‐bond motifs in structures with chiral space groups and the types of groups inducing chirality are discussed. The 2, 3 JX –P ( X = H or C) coupling constants from the NMR spectra of (I) and (II) have been studied. In each compound, the two diastereotopic C6 H5 O groups are different, which is reflected in the different chemical shifts and some coupling constants.